Pendampingang UMKM Kripik Tempe Melalui Inovasi Label dan Kemasan Sebagai Upaya Penyebarluasan Pemasaran di Desa Ingilo-Ilo Kec Slahung, Kab Ponorogo - Rifaannudin, Mahmud; Iliya Ahmad , Zufar (Abdimas Indonesian Journal, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in improving the economy of a region, including in Indonesia. One of the MSME sectors that has great prospects is the food and beverage industry, which is an attraction for the wider community. However, MSMEs in this sector face various challenges, especially in terms of product competitiveness, including packaging quality and legality such as halal certification. This article discusses the mentoring program for the MARWITO Tempe Kripik MSME in Ngilo-Ilo Village, Slahung District, Ponorogo Regency, which aims to improve product competitiveness through packaging innovation and halal label registration. The method used in this activity is direct mentoring, which includes problem identification, routine visits, halal label registration, packaging design updates, billboard creation, and monitoring and evaluation of program results. The results of this mentoring show a significant increase in the legality and marketing aspects of the product, where the MARWITO Tempe Kripik product has successfully obtained halal certification and experienced a change in packaging to be more attractive and professional. The conclusion of this activity is that packaging innovation and halal certification play an important role in increasing the competitiveness of MSMEs in local and national markets. With a more attractive packaging design and fulfilled legality, MSME products are more easily accepted by consumers and have a greater opportunity to grow. This mentoring program is expected to be a model for other MSMEs in improving the quality and marketing of their products.